Effect of Purple Sweet Potato (Ipomoea Batatas L.) on Reducing Renal Tissue Damage of House Mice (Mus Musculus L.) After Excessive Physical Exercise - Sinaga, Rika Nailuvar; Rusmarilin, Herla; Mardiani, T.Helvi; Elvana, Ayu (Indonesian Journal of Medicine, 2016)
Background: Heavy physical exercise can reduce blood flow and metabolism in kidney that eventually release free radicals. The free radicals can form oxydative stress and damage renal tissue. Exogenous antioxydant administration is usually recommended to minimize the renal tissue damage. This study aimed to examined the effect of purple sweet potato (Ipomoiea batatas L.) extract on renal tissue damage in mice (mus musculus L.) after heavy physical exercise.Subjects and Method: This was a randomized controlled trial with post test only control design. The study subjects included twenty four male white mice with DD Webster strain. These mice were divided into six groups. After undergoing excessive swimming exercises that lasted forteen days, purple sweet potato extract was given to the experimental group. There were three experimental groups receiving three different doses of purple sweet potato. The mice kidney was taken as sample for microscopic examination to determine the extent of tissue damage. Difference in renal tissue damage was tested by Kruskal-Wallis.Results: Microscopic examination showed statistically significant difference in tissue damage both in right (p=0.001) and left (p=0.036) kidneys, between study groups. The experimental groups showed less damaged than control group.Conclusion: Purple sweet potato (Ipomoiea batatas L) can lessen renal damage in male white mice (Mus musculus L) undergoing excessive physical exercise.Keywords: purple sweet potato (Ipomoiea batatas L), renal tissue damage miceCorespondance: Rika Nailuvar Sinaga. Faculty of Sport Science, Medan University. Email: rikanailuvar890@gmail.comIndonesian Journal of Medicine (2016), 1(1): 76-83https://doi.org/10.26911/theijmed.2016.01.01.10